Circulating extracellular vesicle‐associated CD163 and CD206 in multiple myeloma. (22nd February 2020) - Kvorning, Sarah L.; Nielsen, Marlene C.; Andersen, Niels F.; Hokland, Marianne; Andersen, Morten N.; Møller, Holger J.
Abstract: Objectives: Extracellular vesicles (EVs) are important for intercellular signalling in cancer. Tumour‐associated macrophages, expressing the haemoglobin‐haptoglobin and mannose receptors CD163 and CD206, are crucial for cancer progression. We recently identified CD163 on EVs in the circulation as a fraction of total soluble CD163 (sCD163). Here, we investigated the presence of CD163 and CD206‐positive EVs (EV‐CD163, EV‐CD206) in patients with multiple myeloma (MM). Methods: We enrolled patients with MM (n = 32), monoclonal gammopathy of undetermined significance (MGUS) (n = 8) and healthy donors (n = 16). Plasma protein levels were determined by ELISA before and after vesicle precipitation. Monocytes were examined by flow cytometry, and leucocyte CD163 mRNA by qPCR. Results: Fractions of EV‐CD163 and EV‐CD206 were significantly elevated in patients with newly diagnosed MM (median = 39.8%, 76.5%, respectively) compared to patients with relapse (15.6%, P  = .02, 42.5%, P  = .003), remission (16.9%, P  < .0001, 25.2%, P  < .0001), MGUS (17.8%, P  < .01, 33.1%, P  = .0005) and healthy donors (14.8%, P  < .0001, 35.5%, P  < .0001). Whole blood CD163 mRNA did not vary between the groups. The intermediate monocyte subset showed a higher CD163 expression in newly diagnosed patients. Conclusions: Our results indicate that macrophage‐derived EVs may play a role in the late phase of malignant progression of MM, and encourage further EV investigations in functional experiments.